DEVELOPING LEARNING CONCEPTS IN PHYSICS ON FORCE AND MOTION DURING THE COVID-19 PANDEMIC THROUGH THE INNOVATION OF A METAVERSE CLASSROOM - Punin, Weera (Journal of Education and Innovation, 2025)
This research aims to develop and design a metaverse classroom for learning mechanics, specifically the concepts of force and motion, considering the limitations and challenges arising during the COVID-19 pandemic. The study also examines the impact of this innovation on the development of concepts and understanding among first-year undergraduate students majoring in physics and assesses their satisfaction and learning experiences. The research findings reveal that the developed metaverse classroom was evaluated as highly effective, with expert approval confirming that it meets the needs of online learning efficiently. This innovation not only bridges theoretical knowledge through virtual experiments but also fosters deep system thinking. Students gained a better understanding of the concepts of force and motion, helping to correct misconceptions and enabling the application of knowledge in diverse contexts effectively. Moreover, students expressed high satisfaction with the learning experience, which offered flexibility, overcame spatial and time limitations, and encouraged active participation between learners and instructors through activities in the metaverse environment. Learning through the metaverse classroom enhanced the understanding of force and motion content and effectively developed essential digital skills for the modern era. This study highlights the high potential of the metaverse classroom innovation in enhancing teaching and learning in situations with limited access to physical classrooms. It can be extended to other disciplines, helping to create a learning environment that supports the development of knowledge, scientific process skills, technology skills, and 21st-century skills in a comprehensive and sustainable manner.